Pengaruh Dana Investasi Melalui Instrumen SUN dan SBSN Terhadap Pertumbuhan Ekonomi Indonesia - Tya Ryandini (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2014)
The Influence of Investment Fund Through National Bond (SUN) and National Sukuk (SBSN) To Economic Growth in Indonesia. The aims of this research is to analyze the short term and long term influence of investment fund through National Bond (SUN) and National Sukuk (SBSN) to economic growth in Indonesia in the year of 2008 – 2012.The methode which used in this research is Error Correction Model. The result shows that economic development is positively influenced by National Bond in short term and long term. But, it negatively influenced by the National Sukuk both in short term and long term DOI:10.15408/aiq.v6i1.1369